Relationship between anthropometric parameters with vertical jump in male elite volleyball players due to game`s position - Fattahi, A.; Ameli, M.; Sadeghi, H.; Mahmoodi, B. (Journal of Human Sport & Exercise, 2012)
Recent study was performed to determine relationship between anthropometric properties with vertical jump on 40 male elite volleyball players (27.93±3.92 years old and 8±1.53 years sport history) in Iran premier league. 42 anthropometric parameters were measured using caliper and flexible tape meter (JAMAR STAINLESS®). In order to decrease parameters covering the same measurements among 42 anthropometric properties, multiple correlation were applied and parameters with coefficient higher than 0.8 were selected for further analysis, so number of parameters decreased to 17. Using principle component analysis method on 17 parameters, three main components including 70% of data variance were extracted. In the main components, parameters with coefficient more than 0.7 including weight, seated height in fixture, shank length, foot length, torso circumference at hip level, maximum calf circumference, abdomen fat, middle tight circumference and tight length were used for further analysis. The difference in distance between the standing reach height and the jump height was measured as the vertical jump records. To determine differences between vertical jump records and also relationship between anthropometric properties with vertical jumps, one way variance analysis (F- Test) and regression coefficients were used. There are significant differences between vertical jump of spikers and liberos, also between setters and liberos, but there are no significant differences between vertical jump of spikers and setters. There is significant relationship between vertical jumps with shank length, maximum calf circumference, foot length for spikers and setters, also tight circumference and weight for liberos.